ROLE OF CLASSICAL UNIVERSITY EDUCATION IN THE FORMATION OF ORGANIZATIONAL CULTURE OF THE SOCIETY - М. Жиленко; М. Свінціцька (Київський національний університет імені Тараса Шевченка, 2017)
In the article the place and the role of classical universities in the social development is being researched. The specialists preparation to the highest levels of the organizational culture of the society on different levels of the development is determined to be carried out by the classical universities. The main determinants which influenced the development of the classical universities education since the first universities foundation till nowadays are being analyzed. Basic models of classical universities, their characteristics, the transformation in accordance with changes of the leading social organizational culture are being studied. It is determined that the aim of classical university on the temporal level is related to the historical time and is represented by its derivative form. Within the dimensional meaning it is demonstrated by the fact that once it is founded as international institution, the university experiences the real blossom as national institution. Since the national state has been built, classical university forms its cultural, ideological and worldview core, and with the beginning of the globalization epoch and active formation of the sole universal educational and research space process it takes the part of the internationalization leader. The tendencies of modern education and the advantages of the classical universities over other types of educational institutions are being studied. The answer to such question is suggested: within the frames of what type of university the problem of the educational relevance to the modern social organizational culture may be solved.The author's understanding of the ways of the native classical university education development is suggested.

Досліджено місце й роль класичних університетів у розвитку людського суспільства. Проаналізовано основні детермінанти, що впливали на розвиток класичної університетської освіти від часів заснування перших університетів дотепер.Розглянуто основні моделі класичних університетів, їхні ознаки, трансформацію відповідно до змін провідної організаційної культури суспільства. Досліджено тенденції сучасної освіти, переваги класичних університетів перед іншими типами вищих навчальних закладів. Запропоновано відповідь на запитання: у межах якого типу навчального закладу може вирішуватися проблема відповідності освіти вимогам сучасної організаційної культури суспільства. Висловлено авторське бачення шляхів розвитку вітчизняної класичної університетської освіти.
РОЛЬ КЛАСИЧНОЇ УНІВЕРСИТЕТСЬКОЇ ОСВІТИ У ФОРМУВАННІ ОРГАНІЗАЦІЙНОЇ КУЛЬТУРИ СУСПІЛЬСТВА
Keywords: університет; ліберальна; утилітарна освіта; організаційна культура суспільства; пошук істини і про- фесійна підготовка; ідеальна модель; спеціалізація класичної освіти; місія гаранта універсальних цінностей і культурного розвитку; university; liberal; practical education; organizational culture of the society; search for truth and professional training; ideal model; classical education specialization; innovative education features; aim of universal values and cultural development guarantee